An Analysis on the Implementation for Covid-19 Vaccine Program in Bogor City Indonesia - Dessy Yuliarty (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2021)
The covid-19 outbreak has been impacted the foundation of human life that encompasses social, economic, political, and environmental including in Bogor city. Bogor government efforts have been undertaken to ameliorate this condition but yet no significant improvement to stop this pandemic. However, the Covid-19 vaccine program initiated by the government has given a positive impact to reduce the positivity rate in Bogor city. Although there are some issues this vaccine program continues to sustain amid uncertainties. This paper, therefore, aims to explore some implementation of the Covid-19 vaccine program in Bogor city and analyze its impact on the positivity rate of Covid-19. To meet this objective, this paper employs a qualitative approach through literature review to unveil the real implementation of the vaccine program in Bogor city. This paper finds that the vaccine program of Covid-19 has not been able to stop completely the Covid-19 outbreak. There are some problems such as literacy and perception of the public towards this vaccine program, the availability of human resources to support this program, and lastly lack of sufficient funds to succeed this vaccine program. This paper implies that hospitals, clinics, and other health institutions must be supported by proper regulation to enhance vaccine programs particularly to provide qualified human resources since the positivity rate tend to increase and sufficient fund in the form of incentives for medical employees.